Some Recent Biblical Re-writings in English and the Contemporary “Canonical” Images of the Bible - Rychter, Ewa (American & British Studies Annual, 2017)
This paper focuses on three contemporary Anglophone rewritings of the Bible (i.e., on Philip Pullman’s The Good Man Jesus and the Scoundrel Christ (2010), Jeanette Winterson’s Boating for Beginners (1985), and on Jim Crace’s Quarantine (1997)) and contends that the rewrites can be read against the background of the late twentieth-century emergence of dominant understandings of the Bible: of the Bible as a cultural icon and of the Bible as an epitome of liberal/human values. Those dominant – or “canonical” – images of the Bible prefer either to foreground the role the Bible played in the formation of Western culture and democracy, and/or to play down the more scandalous, less palatable features of biblical texts. While the dominant images embody the currently most popular and culturally orthodox perspectives on the meaning of the Bible, other concerns and perspectives are relegated to the margins of interest. Seeing some parallels between such contemporary processes of marginalisation/promotion and the past mechanisms of biblical canon-formation, I argue that the recent biblical rewritings re-enact the process of forgetting, suppressing or proscribing alternative accounts of biblical events, and simultaneously, bring into sharp focus and problematize its twentieth- and twenty-first-century form of canonicity.